How would schools step up public health measures to control spread of SARS?. Issue 12 (2nd December 2003) - Lee, A; Cheng, F F K; Yuen, H; Ho, M
Abstract : The severe acute respiratory syndrome (SARS) is a rapidly progressive, and sometime fatal disease with more than 1800 patients in over a dozen countries in Asia, Europe, and North America (including the United States and Canada) within two months. On 12 March 2003, the World Health Organisation (WHO) issued a global alert about SARS so it became a global challenge. Strengthening the public health measures at schools would protect children as well as providing the students an opportunity to learn about infectious disease control through life event approach. The public health measures at schools include two important components: basic understanding of the disease so schools would put on high alert on caution cases, and the measures to improve environmental hygiene at schools and preventive measures to stop infectious disease transmission. This will help to empower the whole community the readiness to deal with other outbreaks in the future.